Redescription of Anthias xanthomaculatus Fourmanoir and Rivaton, and its reassignment in the genus Odontanthias Bleeker (Teleostei: Serranidae: Anthiadinae) - Gill, Anthony C.; Russell, Barry C. (Zootaxa, 2019)
Anthias xanthomaculatus is redescribed from re-examination of the holotype. On the basis of fin shape, meristic details and presence of two closely spaced supraneural bones, it is assigned to the genus Odontanthias Bleeker. It is compared with known Odontanthias species, and shown to be a valid species of the genus and a possible senior synonym of O. grahami Randall & Heemstra. Comparative data for the holotype and three non-type specimens of O. grahami are provided.